Prevalence Rate and Correlation Between Triglyceride Level and Human Body Mass Index in Sulaimani Province, Iraq - Ahmed, Sakar; Ary Bahman Faiq ,; Hama, Abdullah Ahmed; Asmar Hama Salih, (Iraqi Journal of Science, 2021)
The condition of elevated concentrations of ‎triglyceride in ‎the blood is called hypertriglyceridemia, which ‎triggers the onset of some physiological disorder. This study was carried out to find the ‎correlation between body weight and ‎hypertriglyceridemia. ‎Out of 518 cases, 342 individuals were underweight, with body ‎mass index (BMI) values of ≤18, while their mean ‎serum triglyceride level was 172.4 ± 25.2mg/dl. In addition, 99 cases had normal BMI of >18, whereas 60 were overweight (‎BMI = 25-29), with mean serum triglyceride level of 182.3 ± 15.9. Also, 17 cases were obese (BMI >30), where the ‎mean triglyceride level was 202 ± 25.6. The results showed no significant differences in terms of weight categories and triglyceride levels, whereas significant ‎effects of marital status, daily exercise, and diet on elevated triglyceride ‎levels were observed. These findings conclude that underweight and ‎normal BMI individuals were as much at risk of elevated level of triglyceride as overweight and obese ones, which are mostly at higher risk. Moreover, daily exercise and supplementary nutrient have significant effects on triglyceride level.